The back-approach technique of endoscopic saphenous vein harvesting in coronary artery bypass grafting - Tamura, Kiyoshi (Indian J Thorac Cardiovasc Surg, 2020)
PURPOSE: One of the concerns during endoscopic saphenous vein harvesting (EVH) in coronary artery bypass grafting (CABG) is injury to the vein or its branches. The cutting edge of bipolar electrocautery scissors, used to divide the side branches of the saphenous vein, can cause vascular injury leading to reduced graft patency. We have developed a novel back-approach technique using a C-ring to divide the wide side branches of the saphenous vein during EVH. The aim of the study was to describe the technique and assess early outcomes of EVH using this technique. The back-approach technique is as follows: (a) insert the C-ring near the target branch, (b) push the C-ring over the proximal aspect of the target branch, (c) twist the C-ring forward to capture the target branch, and (d) cut the target branch by bipolar electrocautery. METHODS: We investigated 169 patients, including 35 women (mean age 70.1 ± 8.9 years), who underwent CABG at our hospital, using a novel EVH technique. The patients were categorized as those who underwent EVH (EVH group, n = 44) or open vein harvesting (OVH) (OVH group, n = 125). This method involves the creation of a small incision (2 cm), sufficient saphenous vein dissection near the skin incision, adequate dissection to separate the vein from the surrounding tissues, and the back-approach technique with C-ring to divide the side branch of the saphenous vein. The primary endpoint was the graft patency rate, and the secondary endpoints were leg wound complications and length of hospitalization. RESULTS: No significant intergroup difference was observed in early patency of saphenous vein graft patency (OVH vs. EVH = 94.7 vs. 95.6%, p = 0.763). The incidence of lower extremity wound lymphorrhea was significantly lesser (OVH: EVH = 16.0: 0.0%, p = 0.005) and the length of hospitalization was also significantly shorter in the EVH group (OVH vs. EVH = 24.2 ± 9.8 vs. 19.0 ± 5.3 days, p = 0.001). CONCLUSIONS: EVH, using the back-approach technique, showed satisfactory short-term results; therefore, this technique performed with C-ring might be effective for vein harvesting during EVH.